The handbook of the international law of military operations - Gill, Terry D., 1952-; Fleck, Dieter (Oxford University Press, 2015)
Based on best-practice rules of global importance, this handbook offers authoritative commentary and analysis of the international law of military operations, encompassing self-defence, peace operations, and other uses of force.